(untitled) (Research, Society and Development, 2023)
The study aimed to know and analyze the Brazilian political-legal frameworks that deal with alcohol and other drugs in the 21st century. This is a section of the Doctoral Thesis "Therapeutic itineraries of people who use alcohol and other drugs in the city of Teresina, Piauí", defended in 2021 in the Graduate Program in Public Health at the National School of Public Health Sergio Arouca, Oswaldo Cruz Foundation. In this sense, we conducted a qualitative research, based on the assumptions of documentary research, which had as a source of data, the policies, decrees and other regulations that were published in the period 2000 to 2020. The analysis was structured according to the contributions of the psychosocial paradigm. The sectors involved were the Presidency of the Republic, the Ministry of Health, the National Anti-Drug Council, the National Secretariat for Drug Policy, and the Ministry of Justice. Most of the documents were published by Health (14), Presidency of the Republic (12), and Justice (03). Despite the advances, biases, tensions, paradoxes and setbacks, the focus on alcohol and other drugs in the Brazilian legal-political instruments presented an increase in the period studied, with emphasis on harm reduction as the guiding strategy of care. Therefore, in the eye of the anti-manicomial hurricane, the care for people who use alcohol and other drugs urges a kaleidoscopic, holistic vision; it demands new paradigms and concepts, the invention of other ways to intervene and manage services; it requires resistance and an ethical-ethical-critical-political-emancipatory posture, which honors the person as a citizen, protagonist, holder of voice and turn, in fact.